PENGARUH SUHU PENYIMPANAN TERHADAP MINYAK KELAPA TRADISIONAL - Liputo, Siti Aisa; Une, Suryani; Mutsyahidan, Arif Murtaqi Akhmad; Lodi, Sarmila; Ibrahim, Nurfadilah; Tunai, Kasmawati; Malabali, Adinda Putri; Sari, Neneng Puspita (Universitas Negeri Gorontalo, 2024)
The factor that influences cooking oil is the free fatty acid content or free fatty acid, abbreviated as FFA. The levels of freefatty acid components in cooking oil can increase if an oxidation reaction occurs or because it undergoes a hydrolysis reaction. The aim of this research is to determine the effect of free fatty acid content in oil stored at different temperatures. The design used in this research was a Completely Randomized Design (CRD) with one factor where each treatment was repeated 3 times. Based on the research carried out, the results of the Free Fatty Acid test at a temperature of 15℃ were 0.04%. At a temperature of 30℃ the yield was 0.59% and at a temperature of 45℃ the yield was 1.07%. The organoleptic aroma test results that were most popular with panelists were for sample S1 with a storage temperature of 15℃ of 5.40 and the lowest value was at a storage temperature of45℃ with a value of 4.30. The color organoleptic test results that were most popular with panelists were for sample S1 with astorage temperature of 15℃ of 5.30 and the lowest value was at a storage temperature of 45℃ with a value of 2.90.